Kinetics of wettability alteration and droplet detachment from a solid surface by low-salinity: A lattice-Boltzmann method. (1st December 2022) - An, Senyou; Zhan, Yuting; Mahani, Hassan; Niasar, Vahid
Abstract: The dynamics of droplet detachment from a surface is a fundamental topic studied in coating engineering, fluid mechanics, and subsurface engineering applications. This topic has direct relevance to wettability alteration using the modified ionic composition of water in contact with oil droplet, low salinity waterflooding (LSWF). Previous experimental studies of LSWF have shown a very long timescale in wettability alteration which cannot be explained using bulk diffusion coefficient. In the present study, we address both the time scale of detachment, as well as the impact of buoyancy and interfacial forces (referred to as Bond number) on droplet detachment by proposing an advanced GPU-enhanced lattice Boltzmann model. In this model, the immiscible two-phase flow has been coupled with wettability alteration due to the salinity dilution. After full validation of the model against the former experiments, a set of computational setups with distinct Bond numbers were designed to investigate the effect of interfacial tension and droplet size on the dynamics of droplet detachment. Results demonstrate that droplet detachment from a surface is not a unique function of Bond number and diffusion length scale is critical in detachment time. In summary, this study provides a fully validated model of LSWF and delineates the significant difference in impacts of interfacial tension and bubble size on detachment time, which can be used to predict capability for LSWF, to determine favorable conditions, as well as to observe and explain low-salinity-effect. Highlights: A validated lattice-Boltzmann model for two-phase wettability alteration is proposed. Diffusion through thin films seems to control the dynamics of wettability alteration. No unique relation between the Bond number and droplet detachment time was found.